A new genus and species of golden coral (Anthozoa, Octocorallia, Chrysogorgiidae) from the Northwest Atlantic - Cairns, Stephen D. (Zookeys, 2017)
Abstract. A new genus and species of unbranched golden coral, Flagelligorgia gracilis, is described based on several specimens collected off the southeastern coast of the United States. The genus is provisionally included in the family Chrysogorgiidae, pending molecular confirmation. Flagelligorgia morphologically resembles other unbranched chrysogorgiids, such as Distichogorgia, Chalcogorgia, Helicogorgia and Radicipes, to which it is compared. The type species is illustrated and its distribution mapped.